New thermal mineral water from Aguas (Penamacor, Central Portugal): hydrogeochemistry and therapeutic Indications - Gomes, L.M.F. (2019)
Thermal mineral waters are a potential resource in the local and economic development of a region. The thermal area of Termas das Águas is in the inner region of central Portugal and its grant will enable the exploration and exploitation of this water resource for medical and therapeutic purposes through a thermal medical SPA. In Portugal, the classification and legalization of a thermal unit must provide a natural mineral water resource, recognized by Portuguese Energy and Geology General Directorate and integrated in a concession granted by the Portuguese Government. For this purpose, it will be necessary to have available mineral water, with physico-chemical and microbiological, temporal stability, ensuring water’s high quality. The purpose of a certified mineral water includes a detailed geomorphological, geological and hydrogeological characterization of the survey area, as well as the water's compositional temporal stability. Only after the recognition conferred by the national agency as a natural mineral water, it is possible to start a medical-hydrological study, for this resource. This process follows an experimental period of 3 years, during which it is implemented the different and specific balneotherapy techniques associated with the therapeutic features of the mineral water. A final report, to be submitted to Portuguese General Directorate for Health, will gather the main results and conclusions, regarding the benefits of this natural resource on human health, and allow its inclusion as an official medical thermal SPA in the Portuguese Normative Decrees. The main subject of this research is the geological and hydrogeological characterization of Termas das Águas aquifer, as well as the mineral water quality study (AM4 – well). The main topics for the medical hydrological study, mainly related to rheumatic and respiratory diseases, are also presented to the medical SPA of Termas das Águas.